A survey of economic theories and field evidence on pro-social behavior - Stephan Meier (Federal Reserve Bank of Boston, 2006)
In recent years, a large number of economic theories have evolved to explain people's pro-social behavior and the variation in their respective behavior. This paper surveys economic theories on pro-social behavior and presents evidence-mainly from the field-testing these theories. In addition, the survey emphasizes that institutional environment might significantly interact with pro?social preferences and explain some of the variation in observed pro-social behavior.
Keywords: D64; C93; H41; D01; 330